1997
DOI: 10.1074/jbc.272.40.25135
|View full text |Cite
|
Sign up to set email alerts
|

Zyme, a Novel and Potentially Amyloidogenic Enzyme cDNA Isolated from Alzheimer's Disease Brain

Abstract: The deposition of the ␤ amyloid peptide in neuritic plaques and cerebral blood vessels is a hallmark of Alzheimer's disease (AD) pathology. The major component of the amyloid deposit is a 4.2-kDa polypeptide termed amyloid ␤-protein of 39 -43 residues, which is derived from processing of a larger amyloid precursor protein (APP). It is hypothesized that a chymotrypsin-like enzyme is involved in the processing of APP.We have discovered a new serine protease from the AD brain by polymerase chain reaction amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
141
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 28 publications
13
141
0
2
Order By: Relevance
“…Previously, we have demonstrated presence of other kallikreins, including PSA and hK2, in these biologic fluids (20 -27). We have further detected large amounts of hK6 protein in cerebrospinal fluid, which are consistent with the observation that hK6 is expressed at high levels in brain tissue (7). We have further demonstrated presence of hK6 in male and female sera and seminal plasmas and in a small percentage of amniotic fluids and breast tumor cytosols.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously, we have demonstrated presence of other kallikreins, including PSA and hK2, in these biologic fluids (20 -27). We have further detected large amounts of hK6 protein in cerebrospinal fluid, which are consistent with the observation that hK6 is expressed at high levels in brain tissue (7). We have further demonstrated presence of hK6 in male and female sera and seminal plasmas and in a small percentage of amniotic fluids and breast tumor cytosols.…”
Section: Discussionsupporting
confidence: 90%
“…15,16. IMMUNOFLUOROMETRIC ASSAY OF HUMAN KALLIKREIN 6 The newly developed immunofluorometric assay for hK6 may find applications toward the possible diagnostic/prognostic value of this biomarker in various human diseases. More specifically, we are interested to examine if the levels of hK6 in cerebrospinal fluid are associated with Alzheimer's or other degenerative neurologic diseases, as preliminarily suggested by Little et al (7). We are further interested to examine if hK6 concentration in serum or other biologic fluids is altered in various malignancies, with mechanisms similar to those operating for PSA and hK2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously called zyme (Little et al, 1997), protease M (Anisowicz et al, 1996), and neurosin (Yamashiro et al, 1997), kallikrein 6 is now the accepted name (Diamandis et al, 2000b). hK6 is a trypsin-like serine protease of unknown physiologic function that is secreted as a 223 amino acid protein.…”
mentioning
confidence: 99%
“…Various tissues express the hK6 gene and synthesize the protein (Diamandis et al, 2000c;Yousef et al, 1999). Expression is particularly prominent in the brain (Yamashiro et al, 1997), and this, along with the amyloidogenic potential of hK6 (Little et al, 1997) has raised the possibility of a role for hK6 in amyloid precursor processing and the development of Alzheimer's disease. Recently, Diamandis et al (2000d) have shown that hK6 is elevated in the cerebrospinal fluid and blood of individuals with histologically confirmed Alzheimer's, thereby suggesting hK6 may be of value in the diagnosis of this disorder.…”
mentioning
confidence: 99%